Control of American Foul Brood Disease (AFB) in Honey Bee Using Thyme Extracts and Thymol - AL – Jorany, Ridha S.; AL – Kinani, Mohammed A.J.; Abbas, Alaa S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Ethanolic extracts of Thyme (Thymbra spicata) were tested for their inhibitory action on Paenibacillus larvae the causative agent of American foul brood with different concentration by using disc assay and mixed with culture media . Results showd that 3000mg / disc and 3000 mg / ml was the effective concentroation for the both methods .Thymol was isolated by using TLC technique . The effective concentration of thymol on growth of bacteria was 1000 mg / disc .          Thymol and crude extracts of thyme 3000 mg / ml were tested on infected hives by mixed with sugar  solution . The symptoms of AFB disease was full disappearance within 21 , 27 days after treatment with thymol and thyme extracts respectively